Descompuneti in factori:
a) (3x+1)²- (x+3)²
b) (3x+5)² - (x+1)²
c) (x+√2)² - 8
d) (2x+ √3)² - 27
Răspunsuri la întrebare
Răspuns de
21
a) (3x+1)²-(x+3)²=(3x+1+x+3)(3x+1-x-3)=(4x+4)(2x-2)=8(x+1)(x-1)=8(x²-1)
b) (3x+5)² -(x+1)²=(3x+5+x+1)(3x+5-x-1)=
=(4x+6)(2x+4)=2(2x+3)·2(x+2)=4(2x+3)(x+1)
c) (x+√2)² - 8= (x+√2)²- (2√2)²=(x+√2 +2√2)(x+√2-2√2) =(x+3√2)(x-√2)
d) (2x+ √3)² - 27= (2x+√3)²- (3√3)²=(2x+√3+3√3)(2x+√3-3√3)=(2x+4√3)(2x-2√3)
=2(x+2√3)·2(x-√3)=4(x+2√3)(x-√3)
e) (√2x-1)²-32x² = (√2x-1)²-(4√2)²=(√2x-1+4√2)(√2x-1-4√2)
g) x²-2√3x+3 -(y-2√3)²= (x-√3)² -(y-2√3)²= (x-√3+y-2√3)(x-√3-y+2√3)
= (x+y -3√3)(x-y+√3)
b) (3x+5)² -(x+1)²=(3x+5+x+1)(3x+5-x-1)=
=(4x+6)(2x+4)=2(2x+3)·2(x+2)=4(2x+3)(x+1)
c) (x+√2)² - 8= (x+√2)²- (2√2)²=(x+√2 +2√2)(x+√2-2√2) =(x+3√2)(x-√2)
d) (2x+ √3)² - 27= (2x+√3)²- (3√3)²=(2x+√3+3√3)(2x+√3-3√3)=(2x+4√3)(2x-2√3)
=2(x+2√3)·2(x-√3)=4(x+2√3)(x-√3)
e) (√2x-1)²-32x² = (√2x-1)²-(4√2)²=(√2x-1+4√2)(√2x-1-4√2)
g) x²-2√3x+3 -(y-2√3)²= (x-√3)² -(y-2√3)²= (x-√3+y-2√3)(x-√3-y+2√3)
= (x+y -3√3)(x-y+√3)
andreeacristina:
http://brainly.ro/tema/1231761
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Ed. muzicală,
10 ani în urmă
Matematică,
10 ani în urmă